A novel protein complex that regulates active DNA demethylation in Arabidopsis. Issue 4 (17th March 2021) - Liu, Pan; Nie, Wen‐Feng; Xiong, Xiansong; Wang, Yuhua; Jiang, Yuwei; Huang, Pei; Lin, Xueqiang; Qin, Guochen; Huang, Huan; Niu, Qingfeng; Du, Jiamu; Lang, Zhaobo; et al.
Abstract: Active DNA demethylation is critical for altering DNA methylation patterns and regulating gene expression. The 5‐methylcytosine DNA glycosylase/lyase ROS1 initiates a base‐excision repair pathway for active DNA demethylation and is required for the prevention of DNA hypermethylation at 1 000s of genomic regions in Arabidopsis . How ROS1 is regulated and targeted to specific genomic regions is not well understood. Here, we report the discovery of an Arabidopsis protein complex that contains ROS1, regulates ROS1 gene expression, and likely targets the ROS1 protein to specific genomic regions. ROS1 physically interacts with a WD40 domain protein (RWD40), which in turn interacts with a methyl‐DNA binding protein (RMB1) as well as with a zinc finger and homeobox domain protein (RHD1). RMB1 binds to DNA that is methylated in any sequence context, and this binding is necessary for its function in vivo . Loss‐of‐function mutations in RWD40, RMB1, or RHD1 cause DNA hypermethylation at several tested genomic regions independently of the known ROS1 regulator IDM1. Because the hypermethylated genomic regions include the DNA methylation monitoring sequence in the ROS1 promoter, plants mutated in RWD40, RMB1, or RHD1 show increased ROS1 expression. Importantly, ROS1 binding to the ROS1 promoter requires RWD40, RMB1, and RHD1, suggesting that this complex dictates ROS1 targeting to this locus. Our results demonstrate that ROS1 forms a protein complex with RWD40, RMB1, and RHD1, and that this novel complex regulates active DNA demethylation at several endogenous loci in Arabidopsis . Abstract : The DNA demethylase REPRESSOR OF SILENCING1 (ROS1) forms a novel complex with a WD40 domain protein (RWD40), a methyl‐DNA binding protein (RMB1), and a zinc finger and homeobox domain protein (RHD1). This complex regulates DNA demethylation independently of the ROS1 regulator INCREASED DNA METHYLATION1 and regulates ROS1 gene expression.